Implementación de un sistema de gestión de valor compartido en una empresa del rubro yerbatero de la ciudad de Bella Vista (Journal on studies and research of academic knowledge, 2018)
This paper describes the implementation of a Shared Value Management System in a company of the yerba market in the city of Bella Vista. This approach becomes necessary with the purpose of allowing development of future comparisons with the same sector in different countries, at the same time that it will permit to settle a starting point to when posing the reflection of the current situation of the analyzed company in relation to this management system. The objective of this study is to describe the effects produce by the implementation of a shared value management system in a company of the yerba market in the city of Bella Vista of the Itapúa Department. This task was gained from a case study, by applying a research methodology of the nonexperimental type, basic and descriptive with a mixed information nature. The study focused on a company of the yerba market of the city of Bella Vista. The analysis highlighted that most of the workers does not know the shared value management method, this is because the only activity that is carried out is that of Corporate Social Responsibility, moreover there is a confusion between differentiating activities that are essentially a corporate social responsibility entrepreneurship; almost all of the workers agree to elaborate a new product which is innovative and aimed at a social need. Finally, virtually half of the employees mention not knowing limitations to apply this method.
Keywords: Shared value; System; Company